Trends in Male Labor Force Participation and Retirement: Some Evidence on the Role of Pensions and Social Security in the 1970s and 1980s - Anderson, Patricia M.; Gustman, Alan L.; Steinmeier, Thomas L. (Journal of Labor Economics, 1999)
This article estimates the effects of changes in pension plans and social security in the 1970s and 1980s on the steady state retirement of men. Work incentives associated with pension coverage and plan characteristics are calculated primarily from the 1969–79 Retirement History Study and the 1983 and 1989 Surveys of Consumer Finances. Simulations with a structural retirement model suggest that the long‐run effects of changes in pension plans and social security account for about a quarter of the reduction in full‐time work by men in their early sixties but cannot explain the reduction by those age 65.